Concomitant Abdominoplasty and Laparoscopic Umbilical Hernia Repair. (20th April 2018) - van Schalkwyk, Constant P; Dusseldorp, Joseph R; Liang, Derek G; Keshava, Anil; Gilmore, Andrew J; Merten, Steve
Abstract: Background: Umbilical hernia is a common finding in patients undergoing abdominoplasty, especially those who are postpartum with rectus divarication. Concurrent surgical treatment of the umbilical hernia at abdominoplasty presents a "vascular challenge" due to the disruption of dermal blood supply to the umbilicus, leaving the stalk as the sole axis of perfusion. To date, there have been no surgical techniques described to adequately address large umbilical herniae during abdominoplasty. Objectives: To present an effective and safe technique that can address large umbilical herniae during abdominoplasty. Methods: A prospective series of 10 consecutive patients, undergoing concurrent abdominoplasty and laparoscopic umbilical hernia repair between 2014 and 2017 were included in the study. All procedures were performed by the same general surgeon and plastic surgeon at the Macquarie University Hospital in North Ryde, NSW, Australia. Data were collected with approval of our ethics committee. Results: At 12-month follow up there were no instances of umbilical necrosis, wound complications, seroma, or recurrent hernia. The mean body mass index was 23.8 kg/m 2 (range, 16.1-30.1 kg/m 2 ). Rectus divarication ranged from 35 to 80 mm (mean, 53.5 mm). Umbilical hernia repair took a mean of 25.9 minutes to complete (range, 18-35 minutes). Conclusions: We present a technique that avoids incision of the rectus fascia minimizes dissection of the umbilical stalk and is able to provide a gold standard hernia repair with mesh. This procedure is particularly suited to postpartum patients with large herniae (>3-4 cm diameter) and wide rectus divarication, where mesh repair with adequate overlap is the recommended treatment. Level of Evidence: 4: